Philip Vera Cruz : a personal history of Filipino immigrants and the Farmworkers movement - Scharlin, Craig (University of Washington Press, 2000)
"Filipino farm workers sat down in the grape fields of Delano, California, in 1965 and began the strike that brought about a dramatic turn in the long history of farm labor struggles in California. Their efforts led to the creation of the United Farm Workers union under Cesar Chavez, with Philip Vera Cruz as its vice-president and highest-ranking Filipino officer."